2014
DOI: 10.1088/0951-7715/27/3/353
|View full text |Cite
|
Sign up to set email alerts
|

Blenders in centre unstable Hénon-like families: with an application to heterodimensional bifurcations

Abstract: Abstract. We give an explicit family of polynomial maps called center unstable Hénon-like maps and prove that they exhibits blenders for some parametervalues. Using this family, we also prove the occurrence of blenders near certain non-transverse heterodimensional cycles under high regularity assumptions. The proof involves a renormalization scheme along heteroclinic orbits. We also investigate the connection between the blender and the original heterodimensional cycle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…We consider the center-unstable Hénon-like family of endomorphisms G ξ,µ,κ1,κ2 : for some ε > 0. See [14] for a version of this result for blenders (instead of blenderhorseshoes) and [29] for a complete numerical analysis of this family including the study of the creation and annihilation of blenders.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…We consider the center-unstable Hénon-like family of endomorphisms G ξ,µ,κ1,κ2 : for some ε > 0. See [14] for a version of this result for blenders (instead of blenderhorseshoes) and [29] for a complete numerical analysis of this family including the study of the creation and annihilation of blenders.…”
Section: 1mentioning
confidence: 99%
“…The second type of dynamics was studied in [4] (to get infinitely many sinks/sources) and in [5] (to get universal dynamics), and the first type in [15] (where heterodimensional tangencies were introduced). In this paper, we consider heterodimensional tangencies and heterodimensional cycles associated to saddles with non-real eigenvalues, continuing the study started in [14], where a similar configuration (with saddles having real eigenvalues) was considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the authors showed that the C 1 -unfolding of a three dimensional heterodimensional tangency (with k T = 1) leads to C 1robustly non-dominated dynamics and in some cases to very intermingled dynamics related to universal dynamics, for details see [9,6]. In the C r -topologies with r > 1, the bifurcation of such tangencies leads, for instance, to the existence of blender dynamics [8,10]. Kiriki and Soma in [12] obtain the first examples of C 2 -robust heterodimensional tangencies with c T = 1 and k T = d − 2 in any manifold of dimension d ≥ 3.…”
Section: Introductionmentioning
confidence: 99%